Grooming graduates to become business leaders. - New Sunday Times, Shyla Sangaran (2008)
The recent Multimedia Super Corridor (MSC) Malaysia-Institution of higher learning (IHL) Business Plan Competition 2007/08 finals in Kuala Lumpur saw stiff competition among five finalists.